METHODOLOGY OF INTEGRATED TRAINING OF HIGHLY QUALIFIED GYMNASTS - UMAROV Dzhamshid Khasanovich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
This article is devoted to current issues of development and implementation of methods of integrated training of highly qualifed athletes in the feld of artistic gymnastics. Particular emphasis is placed on the technical component of the integrated approach, which determines the key elements of an athlete’s readiness, the level of which directly aﬀects the reliability of performing complex combinations and the artistic perfection of performances within the framework of the next Olympic cycle. The author rightly emphasizes the importance of detailed development and scientifcally based choice of this form of training, since ignoring this aspect often hinders the search for optimal solutions to training problems.